Uterine ageing - YOLDEMİR, AHMET TEVFİK (My University, 2023)
Studies using animal models, have investigated the influence of increasing age on uterine factors that might lead to abnormal decidualization and reduced implantation and defective placentation. The decidual response to a standardized estrogen /progesterone stimulus was reduced in the older animals; whereas, in young rodents decidual response closely resembled the normal decidual response during implantation. Furthermore in rodents, there was a decrease in the expression of endometrial estrogen and progesterone receptor in older ones. Several microRNAs have been associated with the fibrosis process in mice causing age-related uterine dysfunction. Aging of the uteri lead to the downregulation of several genes associated with cell proliferation in mice, indicating impaired proliferation in the presence of senescent cells.In vitro studies of human endometrial stromal cell proliferation revealed that presence of senescent endometrial stromal cells within the endometrium, as well as senescence-associated secretory phenotype secretion which could disturb normal functional activities such as communication with epithelial and endothelial cells, glands formation, vascularization and immune cells attraction. Human endometrial gene expression studies showed that some gene expressions increased as others decreased with age. Likewise some endometrium functions were either up-regulated or down-regulated after 35 years of age. Similarly some ciliary processes were significantly up-regulated in the endometrium of older women (40 years) while some functions associated with cell cycle/ proliferation were down-regulated.The progesterone-governed endometrial transformation is necessary for implantation. Studies which investigated the influence of endometrial ageing on reproductive outcomes in oocyte donation cycles have controversial results. Some authors showed no influence whereas others reported the age-related decline in implantation and pregnancy rates using euploid embryos or young oocyte donors. Lower implantation and live birth rates with fresh donor oocytes for women over 44 years of age were reported when compared to younger recipients. High doses of progesterone could compensate for the abnormal receptivity of aged recipients during oocyte donation. Moreover maternal age over 40 years was associated with a further increase in risk for placental abruption, preterm delivery, low birthweight, intrauterine growth restriction, stillbirth, and perinatal mortality.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kadın Hastalıkları ve Doğum; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Obstetrics and Gynecology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; KADIN HASTALIKLARI & DOĞUM; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; OBSTETRICS & GYNECOLOGY; Cerrahi; Doğum ve Jinekoloji; Surgery